Arsenic contamination in shallow groundwater and agricultural soil of Chakdaha block, West Bengal, India - Shrivastava, Anamika; Barla, Anil; Yadav, Himanshu; Bose, Sutapa (Frontiers in Environmental Science, 2014)
The study area comes in one of the eight districts of West Bengal where groundwater contains arsenic above the prescribed limit by WHO (10μg/l). Each day groundwater is being withdrawn by the village people for the fulfillment of their basic needs and for agricultural purposes. With the groundwater along with high concentration of arsenic (As), many other heavy metals are also getting introduced in the environment. In the areas with a long history of use of such groundwater, the agricultural lands have been affected severely. The extent of contamination has increased to a level where the crops grown in those lands are becoming a major source for arsenic and other heavy metals poisoning and subsequently transfer to different trophic levels. Based on this concern a somewhat detailed study was carried out to obtain an idea about the magnitude of soil and water contamination in the area. The mean concentrations (mg/kg) of As (9.67), Fe (9275.58), Mn (190.04), Cu (26.53) and Zn (36.04) in the control land soils were found within the normal range. Whereas the mean As (54.40), Fe (15745.50), Mn (307.90), Cu (69.33) and Zn (44.56) were found to be in higher, mainly arsenic which is at an alarming point. In case of water samples, the pond water was having the mean concentration (μg/l) of As (32.63), Fe (57.21), Mn (30.25), Cu (0.82). Whereas in case of shallow groundwater there was more increase in the case of As (76.43), Fe (5493.22), Mn (253.63), and Cu (1.825). It was also observed that Zn although present in soil samples, it was below detection limits in case of water samples. The As concentration in soil and water showed a positive correlation. Also the correlation analyses between soil arsenic and other heavy metals shows a positive co-relation with all of them.